Prevention and Treatment of Peritoneal Dialysis-Associated Fibrosis with Intraperitoneal Anti-Fibrotic Therapy in Experimental Peritoneal Fibrosis - Chiao-Yin Sun; Yu-Ting Hsieh; Shang-Chieh Lu; Chi-Ying F. Huang (Pharmaceuticals)
Background/Objectives: Long-term peritoneal dialysis (PD) often results in peritoneal damage and fibrosis, impairing peritoneal membrane function and leading to ultrafiltration failure. This study aimed to explore the therapeutic potential of nintedanib and pirfenidone in preventing and treating PD-associated peritoneal fibrosis using experimental models. Methods: An animal model of peritoneal fibrosis and cultured mesothelial cells were utilized to evaluate the effects of nintedanib and pirfenidone. Histological analysis, molecular techniques, and RNA sequencing were employed to assess the fibrosis, inflammation, and gene expression. The key outcomes included changes in the peritoneal structure, inflammatory markers, and transcriptional regulation. Results: Induced peritoneal fibrosis resulted in significant structural and histological changes. Treatment with nintedanib and pirfenidone effectively prevented peritoneal thickening and reduced excessive fibrosis deposition. Both agents ameliorated the inflammatory responses by lowering inflammatory marker expression, inhibiting cytokine activity, and decreasing macrophage infiltration. Molecular analyses revealed the suppression of inflammation-related transcription regulators and cytokine receptors. RNA sequencing identified glucose-induced gene expression changes and demonstrated significant modulation by the treatments. In animal studies with established fibrosis, these agents reduced peritoneal inflammation and slowed fibrosis progression. Conclusions: This study demonstrates that intraperitoneal administration of nintedanib and pirfenidone shows promise as an anti-fibrosis therapy for preventing and treating peritoneal fibrosis associated with PD. These findings highlight the potential of targeted interventions to improve the long-term outcomes for PD patients.